2013
DOI: 10.1177/1071100713496223
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Comparison of 4 Different Lateral Plate Constructs for Distal Fibula Fractures

Abstract: Identification of an optimal lateral fibular plating system has the potential to improve the clinical outcome of malleolar fracture fixation, particularly when patient conditions are unfavorable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 16 publications
1
24
0
1
Order By: Relevance
“…We believe that the main successful factor is the anatomical reduction and the proper lag screw insertion. Eckel et al demonstrated no significant differences in plate performance ( 16 ): they found positive correlation between bone mineral density and bending stiffness, a negative correlation between BMD and the amount of angulation at the peak bending moment for all plates; one-third tubular plates showed the most high resistance to bending forces. No differences were found in rotational and bending forces, torsional stiffness in external rotation exceeded stiffness in internal rotation; this study did not identify a superior plate.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the main successful factor is the anatomical reduction and the proper lag screw insertion. Eckel et al demonstrated no significant differences in plate performance ( 16 ): they found positive correlation between bone mineral density and bending stiffness, a negative correlation between BMD and the amount of angulation at the peak bending moment for all plates; one-third tubular plates showed the most high resistance to bending forces. No differences were found in rotational and bending forces, torsional stiffness in external rotation exceeded stiffness in internal rotation; this study did not identify a superior plate.…”
Section: Discussionmentioning
confidence: 99%
“…29 Other authors have used measurements of BMD in biomechanical studies. In 2 studies on tibiotalocalcaneal fusions 16,27 and 1 on distal fibula fracture fixation, 8 higher BMD was associated with increased construct stability. However, in 2 studies on tarsometatarsal fusion, no relation was found between BMD and construct stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Once the distal fibula was exposed, a custom jig was used to create a 45-degree oblique osteotomy at the level of the syndesmosis, going from the anterior inferior to the posterior superior fibula aspect. 7…”
Section: Methodsmentioning
confidence: 99%